2011
DOI: 10.1021/jp2049603
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Methane on La2O3 Surfaces Doped with Cu, Mg, or Zn

Abstract: We use density functional theory to examine methane dissociative adsorption on La 2 O 3 substitutionally doped with Cu, Mg, or Zn. We find that these dopants activate the surface oxygen atoms and make methane dissociation exothermic. Cu-doped lanthana is very active, but it loses oxygen too easily and the surface is likely to be reduced at the temperatures at which methane dissociates. The reduced surface has lower activity. The effect of Mg doping on methane activation is less than that of Zn. We focus, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 50 publications
2
38
0
Order By: Relevance
“…Radical intermediates on oxide surfaces are ubiquitous in catalytic oxidation of alkanes and alkenes [55][56][57][58][59] ; yet this chemistry frequently involves C-H scission barriers >1 eV and thus requires high temperatures (>300 o C) in order to achieve appreciable reaction rates. The low barrier in the C-OH scission signifies that radicals can also mediate heterogeneous catalytic processes involving reduction, potentially at much lower temperatures (<200 o C).…”
Section: C-o Bond Hydrogenolysis Active Sitementioning
confidence: 99%
“…Radical intermediates on oxide surfaces are ubiquitous in catalytic oxidation of alkanes and alkenes [55][56][57][58][59] ; yet this chemistry frequently involves C-H scission barriers >1 eV and thus requires high temperatures (>300 o C) in order to achieve appreciable reaction rates. The low barrier in the C-OH scission signifies that radicals can also mediate heterogeneous catalytic processes involving reduction, potentially at much lower temperatures (<200 o C).…”
Section: C-o Bond Hydrogenolysis Active Sitementioning
confidence: 99%
“…Actually, despite the superior catalytic performance of single‐atom catalysts in many reactions of commercial importance, 13,21‐32 the nature of the active phase is not always clear, which is due primarily to the increased complexity in the electronic structure that arises from the change in surface composition 33 . For instance, it has been demonstrated that coadsorption of a pair of amphoteric species (e.g., propyl and H in PDH) could be significantly more stable than the adsorption of the isolated species on many oxide surfaces due to Lewis acid–base interaction, 34‐36 which makes it possible to tailor the catalytic properties of oxides to a particular chemical reaction by doping the surfaces with single metal atoms. In this way, either single metal atoms or their immediate surroundings could make a major contribution to the kinetics of the reaction, 37,38 and sometimes they could even function cooperatively, showing a bifunctional character 39 …”
Section: Introductionmentioning
confidence: 99%
“…Among them, Li-doped MgO 10,[15][16][17][18] and La 2 O 3 -based [19][20][21][22][23][24][25] catalysts have been most studied for oxidative coupling of methane (OCM) using O 2 as an oxidant. Because of the chemical inertness of the CH 4 molecule, these catalysts generally require high operating temperatures (ca.…”
Section: Introductionmentioning
confidence: 99%